Combining VITEK® 2 with colistin agar dilution screening assist timely reporting of colistin susceptibility. (June 2019) - ,; Nutman, A.; Cohen-Percia, S.; Daitch, V.; Babich, T.; Andini, R.; Cuccurullo, S.; Cristinziano, A.; Cavezza, G.; Bertolino, L.; Giuffrè, G.; Giurazza, R.; et al.
Abstract: Objectives: The rise in carbapenem resistance among Gram-negative bacteria has renewed interest in colistin. Recently, the EUCAST-CLSI Polymyxin Breakpoints Working Group declared that broth microdilution (BMD) is the only valid method for colistin susceptibility testing. BMD is not easily incorporated into the routine work of clinical laboratories, and usually this test is incorporated serially, resulting in delayed susceptibility reporting. We tested a strategy of combining VITEK ® 2 with a 2 μg/mL colistin agar dilution (VITEK ® 2/AD) screening plate to improve performance and time to reporting of colistin susceptibility. Methods: Colistin susceptibility for 364 clinical isolates was determined by VITEK ® 2/AD and compared with the reference standard BMD according to the ISO 20776-1:2007 and CLSI guidelines. The EUCAST colistin susceptibility breakpoint of ≤2 μg/mL was used. Escherichia coli NCTC 13846 served as quality control strain. Agreement, very major error (VME) and major error rates were determined using ISO 20776-2:2007. Results: The VME rate for VITEK ® 2 alone was 30.6% (15/49, 95% CI 18.3–45.4%), and was reduced to 10.2% (5/49, 95% CI 3.4–22.2%) using the VITEK ® 2/AD combined testing. The combined testing had categorical agreement with BMD of 97% (354/364, 95% CI 95.0–98.7%), and a major error (ME) rate of 1.6% (5/315, 95% CI 0.5–3.7%). Using the combined testing, even against challenging strains, 349 (95.8%, 95% CI 93.3–97.7%) colistin susceptibility results could be reported, and only 15 isolates required further analysis by BMD. Discussion: Our method is simple to apply and allows rapid reporting of colistin susceptibility.